Developmental expression of glial fibrillary acidic protein mRNA in mouse forebrain germinal zones—implications for stem cell biology - Fox, Irina J.; Paucar, Andres A.; Nakano, Ichiro; Mottahedeh, Jack; Dougherty, Joseph D.; Kornblum, Harley I. (Brain research. Developmental brain research, 2004)
Postnatal neural stem cells (NSCs) express the “traditional” astrocyte marker, glial fibrillary acidic protein (GFAP). Here, we analyze the ontogeny of GFAP mRNA in mouse forebrain germinal zones (GZ). On embryonic day 15, mRNA distribution is highly restricted. Subsequently, expression expands to include many cells in the GZ regions adjacent to the cortex and septum but not to the striatum. Double immunostaining for GFAP and nestin did not demonstrate extensive overlap in the GZ of adult rats, suggesting that either few of the GFAP-expressing cells are stem cells, or that nestin is not a reliable marker for stem cells in the adult rat brain. The current findings indicate that while some GFAP-expressing cells in the GZ may be NSCs, most are not likely to function in a neurogenic capacity.